Eko Kritik Sastra : Perempuan dan Kedaulatan Pangan - rohayati, lia fajar; Suryaman, Maman (Jurnal Pena Indonesia, 2023)
This study analyzes Press Releases on Women's Solidarity, Women and Food Sovereignty using literary eco-criticism or literary ecology. Through an eco-critical perspective, this study seeks to explain the representation of strengthening and food security in maintaining natural resources and the environment for food production in a press release on women's solidarity. This study uses a qualitative method. The results obtained in this study are that in the press release Women's Solidarity encourages improvement in terms of providing understanding to humans so that they are more wise towards ecosystems. The Women's Solidarity Press Release invites the public to be more aware of the environment and food security and increase, foster environmental sustainability of land for strengthening and food security and land tenure. This fact is supported by a series of sustainable policies so that people will prosper. Thus, in relation to ecology as an action that includes: (1) Application of agroecology to the design and management of sustainable agricultural ecosystems. (2) A holistic approach to agriculture and food system development based on traditional knowledge, alternative agriculture, and local food system experience. And (3) Ecological, cultural, economic, and community linkages for sustainable agricultural production, environmental health, and food and community sustainability.